Online customer reviews vs influencer endorsements: Which drives purchase intention through trust? - Harnung Indah Permatasari; Tarysha Aulya Putri Rany; Henny Firizqi; Husban Yarjuna Firdaus (Universitas Sebelas Maret, 2025)
Digital marketing has changed the traditional paradigm, focusing on enhancing product image, competitiveness, and market share through deeper consumer interaction through online platforms. Concentrating on improving product image through features and enhancements, rather than price reduction, is a more eﬀective strategy today. Digital marketing accentuates consumer interaction and brand equity strengthening through platforms facilitating consumer reviews and influencer endorsements. Nonetheless, the influencer's audience fits with the target demographic and the impression they carry needs to be considered by manufacturers. This study addresses the complex relationship between influencer endorsement and online customer reviews on purchase intention combined with trust as a mediator. Data from 333 respondents in Indonesia were analyzed using Structural Equation Modeling (SEM) in SmartPLS. Online reviews, as a form of electronic word-of-mouth (eWOM), significantly influence purchase decisions by increasing trust through objectivity and transparency of product quality and value information. However, influencer endorsement in digital marketing, which is more cost-eﬃcient than conventional media, did not show a significant eﬀect. This research oﬀers important insights for manufacturers in managing their digital marketing strategies by considering the critical role of customer reviews and consumer trust.